The use of coercive measures in a high secure hospital: expressions of institutional and emotional work - Hui, Ada M.L. (2015)
This thesis examines the use and implications of using coercive measures within a high security hospital. High security hospitals are unique environments where challenges are often faced in balancing care with safety and security. The use of coercive measures, namely, restraint, seclusion, rapid tranquillisation and segregation, are considered unavoidable necessities in preventing and/or limiting harm. Yet coercive measures are deemed ethically, morally and professionally controversial.